Successful treatment of acute inflammatory cardiomyopathy in a young patient with COVID-19: a clinical case - O. V. Soldatova; I. Ya. Goryanskaya (Рациональная фармакотерапия в кардиологии, 2025)
Myocardial injury in COronaVIrus Disease 2019 (COVID-19) mainly occurs in young and middle-aged men and is associated with severe course, unfavorable prognosis and high hospital mortality, especially in combination with elevated troponin and brain natriuretic peptide (BNP) levels. Cardiovascular manifestations may occur in the acute period of the disease or later, have short-term (cardiogenic shock, tachyarrhythmias, acute heart failure) and long-term consequences (transformation into dilated cardiomyopathy, chronic heart failure), ultimately contributing to adverse outcomes. We present a clinical case of a young male admitted to the intensive care unit with the acute left ventricular failure (pulmonary edema). The examination revealed elevated myocardial injury markers, dilation of all heart chambers, and reduced left ventricular ejection fraction (LVEF) to 30%, indicating myocardial dysfunction. Increased pro-inflammatory markers confirmed its inflammatory origin. A significantly elevated N-terminal pro- BNP (NT-proBNP) level and clinical signs of pulmonary edema indicated acute left ventricular failure (Killip III). The background disease: severe COVID-19 complicated by inflammatory cardiomyopathy, acute heart failure Killip III. Due to timely initiated pathogenetic therapy, the patient’s condition was stabilized and a fatal outcome was avoided despite the poor prognosis. Three-month post-discharge follow-up revealed positive trends, including thrombus resolution in the cardiac cavity, disappearance of inflammation signs, and a slight increase in LVEF, suggesting gradual regression of myocardial injury.